Book Review: Mentoring Companionship - Davin Giovanni (Sekolah Tinggi Teologi Baptis Indonesia, 2022)
Freddy Lay’s book conveys a new approach towards mentoring service, which is Mentoring Companionship. It is an accompaniment which based on relational mutual trust, commitment, and humility to be able to mentor and to be responsible to one another. Based on his book, Lay’s offers 4 models of Mentoring Companionship, such as: Mentoring man-to-man, Group Mentoring, Couples Mentoring, and Group Couples Mentoring. Moreover, according to Lay, these 4 models are applicable towards six categories of couples mentoring which are: mentoring for fellow Former Pastors, mentoring for fellow God’s servants, mentoring for fellow workers and professionals, mentoring for fellow church’s volunteers, mentoring for fellow family members, and specific mentoring for elderly by the younger member as mentors.